(3eNJUQ aj UfGYI GdWHs
(3ChdgG (B:s
(3fMeO Gddg Ydi eG gOGfG SHjd GdQTGO hHYO agPG eNJUQ ai UfGYI GdWH CdaJg dHYV GdeJYdejf hChOYJg ahGFO ZQjHI haQGFO YLjHI s
(3BNQgG (B:s
(3hGdbeQ eJUd HGdeTJQi hGdRgQI hgeG ahb GdCQV Je HYhf Gddg s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdYGTQIs
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdWHs